The effect of high-speed dental handpiece coolant delivery and design on aerosol and droplet production. (September 2021) - Allison, James R; Edwards, David C; Bowes, Charlotte; Pickering, Kimberley; Dowson, Christopher; Stone, Simon J; Lumb, Joanna; Durham, Justin; Jakubovics, Nicholas; Holliday, Richard
Abstract: Objectives: High-speed dental instruments produce aerosol and droplets. The objective of this study was to evaluate aerosol and droplet production from a novel electric micromotor handpiece (without compressed air coolant) in real world clinical settings. Methods: 10-minute upper incisor crown preparations were performed in triplicate in an open-plan clinic with mechanical ventilation providing 3.45 air changes per hour. A 1:5 ratio electric micromotor handpiece which allows water coolant without compressed air (Ti-Max Z95L, NSK) was used at three speeds: 60, 000 (60 K), 120, 000 (120 K), and 200, 000 (200 K) revolutions per minute. Coolant solutions contained fluorescein sodium as a tracer (2.65 mmol L   −   1 ). High-speed air-turbine positive control, and negative control conditions were conducted. Aerosol production was evaluated at 3 locations (0.5 m, 1.5 m, and 1.7 m) using: (1) an optical particle counter (OPC; 3016-IAQ, Lighthouse) to detect all aerosol; and (2) a liquid cyclone air sampler (BioSampler, SKC Ltd.) to detect aerosolised fluorescein, which was quantified by spectrofluorometric analysis. Settled droplets were detected by spectrofluorometric analysis of filter papers placed onto a rig across the open-plan clinic. Results: Local (within treatment bay) settled droplet contamination was elevated above negative control for all conditions, with no difference between conditions. Settled droplet contamination was not detected above negative controls outside the treatment bay for any condition. Aerosol detection at 1.5 m and 1.7 m, was only increased for the air-turbine positive control condition. At 0.5 m, aerosol levels were highly elevated for the air-turbine, minimally elevated for 200 K and 120 K, and not elevated for 60 K. Conclusions: Electric micromotor handpieces which use water-jet coolant alone without compressed air produce localised (within treatment bay) droplet contamination, but are unlikely to produce aerosol contamination beyond the immediate treatment area (1.5 m), allowing them to be used safely in most open-plan clinic settings.